When Utilitarian Claims Backfire: Advertising Content and the Uptake of Insects as Food - Berger, Sebastian; Bärtsch, Christian; Schmidt, Christina; Christandl, Fabian; Wyss, Annika M. (Frontiers in Nutrition, 2018)
A key challenge for climate change mitigation on the consumer side is to break habits that excessively lead to carbon emission. One of the culturally most robust human routines is the excessive reliance of the Western societies on conventional meat sources beef, pork, and poultry, which were recently accused of particularly high climate costs. In this light, the UN (FAO) has suggested the increasing use of insects as an alternative source of animal protein intended for human diets. Yet, insects have not reached the mainstream of Western cuisine. Up to day, a frequent promotion strategy of insects is to highlight the Utilitarian benefits associated with their consumption (e.g., with respect to the environment or one’s health). The present research addresses the efficacy of such claims in a consumer research study involving 180 participants recruited from the general population in Germany. Arguing based on social-cognitive research in the area of moral and environmental psychology, we hypothesized and found that a focus on beneficial, but temporally distant motives (e.g., health) – counterintuitively – decreases consumption in comparison to immediate, hedonic advertisements (e.g., tasty). Furthermore, our study provides process evidence suggesting pretrial expectations induced by a particular claim mediate the relationship between claims and consumption. Thus, the present research not only refutes a state-of-the-art approach in the promotion of insects as food, provides an alternative approach, and also provides process evidence by integrating psychological factors.